Cooking an ontology - Ribeiro, R.; Batista, F.; Paulo, J.; Mamede, N.; Pinto, H. (AIMSA 2006: Artificial intelligence: methodology, systems, and applications, Conference proceedings, 2006)
An effective solution to the problem of extending a dialogue system to new knowledge domains requires a clear separation between the knowledge and the system: as ontologies are used to conceptualize information, they can be used as a means to improve the separation between the dialogue system and the domain information. This paper presents the development of an ontology for the cooking domain, to be integrated in a dialog system. The ontology comprehends four main modules covering the key concepts of the cooking domain – actions, food, recipes, and utensils – and three auxiliary modules – units and measures, equivalencies and plate types.